Internationalisation of Higher Education: The Activity – Process Approach at Universiti Tun Hussein Onn Malaysia - Nurshaidah Mohamad Sari; Nur Sofurah Mohd Faiz (Universitas Pendidikan Indonesia (UPI), 2021)
Internationalisation of higher education definition has evolved and so are the approaches in its implementation. The internationalisation of higher education is executed either one of the two approaches, the activity or the process approach, including in the higher education institutions in Malaysia. By giving the attention on one approach alone could contribute to issues in the less focused approach and hinder institutions from receiving maximum benefit from internationalisation. Thus, this study explores the nature of internationalisation approaches in the experiences of meso-level professionals and individuals in the micro level of the institution, specifically at the Universiti Tun Hussein Onn Malaysia (UTHM). The qualitative case study is adopted to gain adequate information from the internationalisation actors of the institution. The information is collected through face-to-face interviews, participatory observations, and documents analysis. Literature found that most of the higher education institutions practiced the activity approach in the implementation of internationalisation at the majority of higher education institutions. This should also happen to the internationalisation practices at UTHM where the execution is driven by the meso-level professionals of the institution. However, internationalisation experts have long promoted internationalisation practices to be in a dynamic activity – process fashion. Result of this study offers the policymakers, internationalisation key actors and stakeholders, valuable information on the internationalisation approaches to serve as a guideline in measuring the internationalisation practices, strategies development and quality improvement in the higher education system in Malaysia.